An efficient method for modeling and evaluating the bench terrain of open-pit mines - Wang, Bonan; Gong, Bing; Xu, Wei; Shi, Xiaoshan (Frontiers in Earth Science, 2024)
In order to quantitatively analyze the roughness of the bench floor during open pit mine blasting, this study proposes a real-time measuring method for the three-dimensional terrain of the bench floor during the excavation process. Real-time monitoring is conducted on the boundary and internal discrete points of the workbench floor during electric shovel operation, utilizing real-time kinematic global navigation satellite system (RTK-GNSS) positioning technology. An improved convex hull algorithm is introduced to automatically extract the optimal boundary of discrete point clouds based on their spatial distribution characteristics. The study establishes a digital elevation model (DEM) using five interpolation algorithms for 3D terrain visualization simulation. Through cross validation, a comparative analysis of the DEM accuracy showed that the simulation results of the Ordinary Kriging interpolation algorithm were found to be optimized. The optimized interpolation algorithm is applied to simulate the 3D terrain in the Dexing open-pit copper mine and the relevant terrain parameters were calculated. This dataset serves as a precise foundation for real-time path planning of elevation blasting design and ground leveling operations.